(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
While metadata has been a strong focus within information professionals‟ publications, projects, and initiatives during the last two decades, a significant number of domain-specific markup languages have also been developing on a parallel path at the same rate as metadata standards; yet, they do not receive comparable attention. This essay discusses the functions of these two kinds of approaches in scientific resource discovery and points out their potential complementary roles through appropriate interoperability approaches. link para o texto completo: www.periodicos.ufsc.br/index.php/eb/article/view/16890/15768